State and local public finance - Fisher, Ronald C (Thomson, 2007)
Get the Finance textbook that covers complex policy issues using easy-to-understand concepts! STATE AND LOCAL PUBLIC FINANCE provides you with a clear analysis of federal finance practices, and it focuses on state and local government policy as well. Because it's uncomplicated and yet thorough, STATE AND LOCAL FINANCE is perfect for anyone from economics majors early in their studies to graduate students in Public Administration.